A comparison of patient satisfaction between treatment with conventional complete dentures and overdentures in the elderly: a literature review - Assunção, Wirley Goncalves [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Delben, Juliana Aparecida [UNESP]; Gomes, Erica Alves [UNESP]; Tabata, Lucas Fernando [UNESP] (Wiley-Blackwell, 2010)
Background:It has been stated that mandibular overdentures are more satisfactory than conventional dentures, but problems relating to the use of retrospective ratings, lack of control group and sequential provision of treatment may compromise the findings.Objective:To establish a comparison between treatment with conventional complete dentures and implant-retained overdentures in elderly patients by conducting a literature review.Materials and methods:A search of English language peer-review literature was completed using Medline up to 2008 focusing on evidence-based research. Randomised clinical trials (RCTs) and longitudinal prospective studies were favoured in the review, using a general hierarchical classification. Articles that did not focus exclusively on the comparison of patient satisfaction between complete dentures and overdentures were excluded from further evaluation. The last search was conducted in February 2008. Key terms included quality of life, patient satisfaction, edentulism, complete denture and overdenture.Results:Among the 90 articles found in the initial search, 27 met the inclusion criteria. This included 18 RCTs and eight prospective and one cohort study. Most of the articles stated superiority of the mandibular implant-retained overdenture therapy over the conventional complete denture regarding patient satisfaction and quality of life.Conclusion:Even with implant treatment presenting higher patient satisfaction and improvement of quality of life, it was not possible to establish a direct comparison between the studies due to differences in adopted methodologies.
Keywords: elderly; complete denture; overdenture; quality of life; patient satisfaction